1988
DOI: 10.1002/crat.2170231027
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of two quenched CuInSe phases

Abstract: The crystal structures of the S-phase with a composition of Cu0.~~Inl.l&3e2.00 and of a Cupoor p-phase with a composition of Cu0.3&11.20Se2.00, both quenched from 750 O C , have been determined with single crystals. The S-phase crystallizes with a = 576.2(4) pm in the ZnStype structure (space group F43m). the /?-phase with a = 5 7 5 4 3 ) pm, c = 1152.0(4) pm and Z = 4 in a new structure type for tetrahedral structures with the space group PZ2c. In both compounds the cations are statistically distributed toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 14 publications
4
57
0
1
Order By: Relevance
“…ODC-related phases, comparing to that of the chalcopyrite structure. 15,16 This finding is consistent with results of several authors: a continuous decrease of the tetragonal unit cell parameter as a function of Cu-deficiency in the film has been reported for the Cu(In,Ga)Se 2 single crystal 17 and also for physical vapor deposited Cu(In, Ga)Se 2 thin film. 18 The reduction of the lattice parameter was attributed to the structural modification to more Cu-poor phases.…”
Section: þ2supporting
confidence: 91%
See 1 more Smart Citation
“…ODC-related phases, comparing to that of the chalcopyrite structure. 15,16 This finding is consistent with results of several authors: a continuous decrease of the tetragonal unit cell parameter as a function of Cu-deficiency in the film has been reported for the Cu(In,Ga)Se 2 single crystal 17 and also for physical vapor deposited Cu(In, Ga)Se 2 thin film. 18 The reduction of the lattice parameter was attributed to the structural modification to more Cu-poor phases.…”
Section: þ2supporting
confidence: 91%
“…It should to be mentioned that the crystal structure of both CuGa 2 Se 3.5 and CuGa 3 Se 5 are almost similar, belonging to the same space group with almost similar lattice parameters and consequently, having a peak position at the same 2h value in their corresponding X-ray diffraction profiles. 15,16 Therefore, it is difficult to differentiate between these two phases from the XRD pattern. Consequently, the term 'ODC-phase' is applicable to both of these phases interchangeably in the discussion of x-ray diffraction results.…”
Section: þ2mentioning
confidence: 99%
“…They are sometimes referred to as P-chalcopyrite, a term coined by Hönle and coworkers when they concluded that the structure possesses P42c symmetry [46]. These structures are also sometimes referred to generically as "Ordered Defect Compounds" (ODC's) but it is important to understand that "ordering" in the context of this terminology refers to the regular arrangement of preferred crystallographic sites on which defects are found, which alters the symmetry properties of the lattice.…”
Section: β β β β-Cis (Cu2in4se7 and Cuin3se5)mentioning
confidence: 99%
“…The ternary semiconductor compound CuIn 7 Se 11 belongs to defect semiconductors of A I-B III 2n+1 C VI 3n+2 type formed on Cu 2 Se-In 2 Se 3 quasi-binary section at n = 3 [1][2][3]. Such semiconductors are promising materials for creation on their basis of a number of semiconductor devices, such as infrared and visible radiation sources, high efficient and high radiative-resistant thin film solar cells and other devices of semiconductor and quantum electronics [4][5][6].…”
Section: Introductionmentioning
confidence: 99%